A Comprehensive Review on Pharmacological Properties of Tectona Grandis. Linn - Shava Ansari; Shweta Gupta; Sabiha Iram; Dr. Shiv Dev Singh (International Journal of Scientific Research in Science and Technology, 2025)
Tectona grandis is a huge deciduous tree that is found throughout Myanmar Southeast Asia, and the Indian subcontinent and is a member of the Lamiaceae family. Traditionally, various parts of the plant, including its root, seed, flowers, leaves, and bark, have been used in folk medicine for treating ailments such as ulcers, diabetes, inflammation, skin disorders, and microbial infections. The phytochemical composition of Tectona grandis is highly diverse, encompassing naphthoquinones, anthraquinones, flavonoids, terpenoids, alkaloids, phenolic acids, and saponins, which are responsible for its extensive pharmacological properties. This review compiles and critically analyzes the therapeutic potential of Tectona grandis, focusing on its anti-ulcerogenic, cytotoxic, antihyperglycemic, antifungal, antioxidant, antimicrobial, antiasthmatic, anticonvulsant, analgesic, and diuretic activities. Additionally, its role in hair growth stimulation and nutritional benefits is discussed. Furthermore, recent advancements in the synthesis of metal nanoparticles from Tectona grandis extracts have demonstrated promising applications in antimicrobial and cytotoxic therapies.
Keywords: Tectona grandis; Antidiabetic; Hair growth; Cytotoxic; Nanoparticle; Bioactive Phytoconstituents